2015
DOI: 10.1590/0102-311x00069514
|View full text |Cite
|
Sign up to set email alerts
|

Social context of neighborhood and socioeconomic status on leisure-time physical activity in a Brazilian urban center: The BH Health Study

Abstract: This study aimed to estimate the prevalence of leisure-time physical activity and investigate its association with contextual characteristics of the social and physical environment in different socioeconomic statuses, using a household survey in Belo Horizonte, Minas Gerais State, Brazil (2008-2009). Leisure-time physical activity was measured by the International Physical Activity Questionnaire; and the social and physical environment by scales arising from perception of neighborhood attributes. Multilevel lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
2
16
1
1
Order By: Relevance
“…For instance, in Brazil, daily consumption of sodium is more than twice (4.7 g per 2000 kcal) the recommended levels of intake according to the World Health Organization [23]. In addition, despite the fact that around 60% of the sample of this study reported being physically active (data not shown), sedentary lifestyle in leisure-time is high (around 65% of the people) among Brazilians [5, 24]. Of note, incidence of hypertension and other cardiovascular and metabolic diseases is growing worldwide.…”
Section: Discussionmentioning
confidence: 87%
“…For instance, in Brazil, daily consumption of sodium is more than twice (4.7 g per 2000 kcal) the recommended levels of intake according to the World Health Organization [23]. In addition, despite the fact that around 60% of the sample of this study reported being physically active (data not shown), sedentary lifestyle in leisure-time is high (around 65% of the people) among Brazilians [5, 24]. Of note, incidence of hypertension and other cardiovascular and metabolic diseases is growing worldwide.…”
Section: Discussionmentioning
confidence: 87%
“…The study was approved by the Research Ethics Committee of the Federal University of Minas Gerais 17,19 . Further details can be found in prior studies 10,16,17,19 . MOVE-SE Academias (2014-15) study "The MOVE-SE Academias (2014-15) study" integrates the umbrella project "Health Academy: evaluation of physical activity promotion programs in Brazil", and monitors the implementation of the program as to management, governance and impact, according to the "Strategic Action Plan for Tackling Chronic Non-communicable Diseases in Brazil -2011-2022" 14 .…”
Section: Data Basementioning
confidence: 99%
“…Increasing access to public areas for physical activities or sports has been an urban policy to encourage such practice 2 . The density and proximity of sports and leisure equipment 9 , as well as a better evaluation of the environment 10 have already been associated with physical activity. However, the distribution of these facilitators is an important social-spatial segregation factor 11 , especially, within the context of Latin America 12 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, neighbourhood rates of homicides have been linked to obesity in Cali, Colombia19 and Belo Horizonte, Brazil,20 whereas perceiving one’s neighbourhood as unsafe was associated with decreased physical activity in Curitiba, Brazil,6 Sao Paulo, Brazil,21 and Florianopolis, Brazil 7. To our knowledge, no studies in Latin America have looked into neighbourhood social interactions—measured by social cohesion or social ties—and obesity,4 but a study in Belo Horizonte, Brazil found that neighbourhood social cohesion was positively associated with physical activity 22…”
Section: Introductionmentioning
confidence: 97%